The Effect of Intellectual Capital and Corporate Social Responsibility on Company Performance (Empirical Study on Banking Companies Listed on the Indonesia Stock Exchange in 2013-2017) - Yunia Oktari; Liugowati Liugowati (eCo-Fin, 2019)
In the current era of globalization, the world economy is growing so rapidly. Companies must change their business moving towards a knowledge-based businesse. Therefore, companies increasingly emphasize the importance of knowledge assets. One approach used in the assessment and measurement of knowledge assets is Intellectual Capital (IC). The company's performance is a major factor in determining the success of a company. A good company determined by a good performance. The purpose of this research was to obtain empirical evidence about the influence of intellectual capital and corporate social responsibility to company’s performance. Intellectual capital is measured by VAICTM. Corporate social responsibility is measured by CSRIj. Meanwhile, company performance is measured by Return on Equity (ROE). The sample used in this research are 22 banking companies listed on the Indonesia Stock Exchange in 2013–2017 and using the secondary data from their listed and published annual report at Indonesia Stock Exchange. The method used in the determination of sample is purposive sampling. Data analysis technique in this research is classical assumption test and hypothesis test by using multiple linear regression analysis. Based on the results it shows that intellectual capital has a positive and significant impact to company’s performance. Corporate social responsibility has a positive and significant impact to company’s performance. Intellectual capital and Corporate social responsibility certainly stimulate to give a significant effect to company’s performance